Hydroclimate variability of the northwestern Amazon Basin near the Andean foothills of Peru related to the South American Monsoon System during the last 1600 years - Apaéstegui Campos, James Emiliano (2014)
In this paper we explore a speleothem δ¹⁸O record from Palestina Cave, North Eastern Peru, at a site on the eastern side of the Andes cordillera, upper Amazon Basin, interpreted as a proxy for South America Summer Monsoon (SASM) intensity. This record 5 allows reconstructing SASM activity with ∼ 5 yr time resolution over the last 1600 yr, spanning two major periods of climate variability: the Medieval Climate Anomaly (MCA; 900–1200 AD) and Little Ice Age (LIA 1400–1850 AD) recognized as periods of decrease and increase SASM activity respectively. Time series and wavelet analyses reveal decadal to multidecadal frequencies. Our results suggest that Atlantic Multi10 decadal Oscillation mode (AMO) plays an important role for SASM modulation on multidecadal scale (∼ 65 yr), especially over dry periods such as observed during MCA. Frequencies of 8 and 25 yr simultaneously with multidecadal signal (65 yr) are found over the LIA. and suggest that those modes could be related to North Atlantic Oscillation (NAO) and Interdecadal Pacific Oscillation mode (IPO). Comparison with other 15 South American Paleoprecipitation records shows that the Atlantic and Pacific decadal to multidecadal variability and their teleconnections play an important role in the intensity and the regional patterns of rainfall distribution during the last 1600 yr.